Penerapan Teori Belajar Konstruktivisme Menurut Jean Piaget dalam Pembelajaran Pendidikan Agama Katolik bagi Generasi Alpha - Sergius Lay; Yessi Florentina Pasaribu; Martina Rosmaulina Marbun; Paulinus Kanisius Ndoa (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2025)
The title raised in the research is the implementation of constructivism learning theory according to Jean Piaget in Catholic religious education learning for the Alpha generation. The method used in this research is literature review research. While the purpose of this research is to find out how to apply constructivism learning theory according to Jean Piaget in Catholic religious education learning for the Alpha generation. Simply put, it can be explained that Piaget stated that learning is an active construction in which individuals continuously adapt to their environment. Catholic religious education aims to instill universal values such as love, justice, and peace, and encourage students to practice them in everyday life. The Alpha generation, which grew up in the digital era, has a very close relationship with technology. Based on the theory of constructivism, Jean Piaget identified three main principles in learning, namely active learning, social learning, and learning through direct experience. These principles can be implemented and applied in Catholic religious learning. The application of constructivism learning theory according to Jean Piaget in Catholic religious education learning for the alpha generation can make learning activities or processes varied and effective, especially if students are directly involved in the learning process through experience and are able to create new concepts based on experiences experienced by students. So that the objectives of Catholic religious education learning can be achieved properly.